1975
DOI: 10.1128/jcm.1.2.206-211.1975
|View full text |Cite
|
Sign up to set email alerts
|

Pagano-Levin Candida test medium: evaluation using vaginal samples

Abstract: Since 1958 Pagano-Levin medium (PLM) has been used as an aid in the identification of Candida albicans. However, no statistical analysis of its effectiveness based on large number of random human specimens has been reported. The present study compared PLM (now called Candida test) with Sabouraud's plus antimicrobials and Littman's ox-gall agar without antimicrobials. Of 500 random vaginal samples 24.8 were true positives, 71.9% were true negatives, 2.2% were false positives, and 1.2% were false negatives on PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…PAGNO et al (65) have described a medium which allows various yeast species to be distinguished through visual differences in coloration, facilitated by a reduction of triphenyltetrazolium chloride incorporated into Sabouraud's agar. A number of subsequent studies have demonstrated that Pagano-Levin medium is useful for retrieval of multiple yeast species from a single clinical specimen (66)(67)(68)(69).…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…PAGNO et al (65) have described a medium which allows various yeast species to be distinguished through visual differences in coloration, facilitated by a reduction of triphenyltetrazolium chloride incorporated into Sabouraud's agar. A number of subsequent studies have demonstrated that Pagano-Levin medium is useful for retrieval of multiple yeast species from a single clinical specimen (66)(67)(68)(69).…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…We found relatively few false-positive and false-negative results, 5 and 10, respectively. This is excellent when compared with the reported efficacy of the other primary isolation media (those of Nickerson [12] and Pagano et al [15]) (13,18,21).…”
Section: Discussionmentioning
confidence: 54%